2011
DOI: 10.1103/physrevb.83.140509
|View full text |Cite
|
Sign up to set email alerts
|

Competition of pairing symmetries and a mechanism for Berezinskii pairing in quasi-one-dimensional systems

Abstract: We revisit the pairing symmetry competition in quasi-one-dimensional systems. We show that spin-triplet s-wave pairing, where the pair is formed by electrons with different times and has an odd-frequency symmetry, can be realized in systems with one-dimensionality when the strength of charge fluctuation exceeds that of spin fluctuation. The present study provides a mechanism for this exotic pairing proposed by Berezinskii [JETP Lett. 20, 287 (1974)].

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 23 publications
2
40
0
Order By: Relevance
“…OTE states have previously been discussed in the context of disordered 2D electron systems [42]. For a quasi-1D system such as we have here, a field-induced transition from OSO to OTE pairing is found in theoretical studies based on the extended Hubbard model, due to enhancement of charge fluctuations over spin fluctuations [43][44][45]. The two possible H-SC states could be distinguished by studying the effect of disorder on T c within the H-SC phase, but such studies to date have only measured the L-SC phase [36,37].…”
Section: Prl 110 107005 (2013) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 67%
“…OTE states have previously been discussed in the context of disordered 2D electron systems [42]. For a quasi-1D system such as we have here, a field-induced transition from OSO to OTE pairing is found in theoretical studies based on the extended Hubbard model, due to enhancement of charge fluctuations over spin fluctuations [43][44][45]. The two possible H-SC states could be distinguished by studying the effect of disorder on T c within the H-SC phase, but such studies to date have only measured the L-SC phase [36,37].…”
Section: Prl 110 107005 (2013) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 67%
“…Theoretically possible realizations of the OF superconductivity in bulk systems are proposed in electron systems such as the t-J model [4], Kondo and Anderson lattices [5][6][7][8][9][10][11][12][13][14][15][16], geometrically frustrated system [17], quantum critical regime [18][19][20], quasi-one-dimensional systems [21][22][23][24], and electron-phonon coupled systems [25,26]. However, using mean-field-type theory, it has been shown that the second-order phase transition into the OF superconductivity is unstable in general [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…After that, Balatsky and Abrahams suggested an odd-ω spin-singlet pairing state 14 in a study on high-T C cuprates while, of course, the consensus is now that a conventional even-frequency (even-ω) spin-singlet d-wave pairing state is realized in the high-T C cuprates. A lot of intensive studies on the odd-ω pairing state follow these proposals in both bulk [15][16][17][18][19][20][21][22] and inhomogeneous systems. [23][24][25][26][27] Since there have been predicted many anomalous novel quantum phenomena in odd-ω pairings generated in inhomogeneous systems, [28][29][30][31][32][33][34][35][36][37][38] it is a challenging issue to pursue the possible bulk odd-ω superconductor from various aspects now.…”
Section: Introductionmentioning
confidence: 82%
“…In the presence of the staggered field, however, the cancellation is broken and the charge-χ is considerable. Especially in the large h s region, only one element χ bub,AA ↓↓ is effective and the charge-χ (19) becomes comparable to the L-spin-χ (18). The growth of only one element χ bub,AA ↓↓ is caused by the fact that a sublattice A is ↓-spin-rich in the staggered field.…”
Section: B Mechanism Of Ots Pairing In a Staggered Fieldmentioning
confidence: 99%